The Effect Of Brisk Walking Exercise On Reducing High Blood Pressure In Hypertension Patients - Suci Anggraeni,; Silvia Nurfadila Trisnawati, (Journal of Health Science Community, 2025)
The development of society with a modern lifestyle like today is not always beneficial but can be detrimental to human life, causing individuals to be exposed to infectious and non-communicable diseases. Several non-communicable diseases that cause high mortality and morbidity include stroke, cardiovascular disease and diabetes. The aim of this study was to determine the effect of brisk walking exercise on reducing high blood pressure in hypertensive patients at Posbindu Gemaharjo. The research design used was Quasy Experimental with a Pretest Posttest Control Group Design approach. The population in the study was 40 potential respondents, the sampling technique used was accidental sampling, the sample size obtained was 28 respondents who would be divided into two groups, 14 control groups and 14 treatment groups. The average blood pressure value before brisk walking exercise was carried out in patients taking hypertension medication at Posbindu Gemaharjo was 162.07, the diastole value was 107.7 and after the intervention the systole value was 133.07 and the diastole value was 94.9. Meanwhile, in the group that only took hypertension medication, the average systole value was 159.71 and the diastole value was 107.93 and the post test results showed that the diastole value was 131.00 and the diastole value was 90.79. The statistical test results for both groups obtained a value of p=0.000 (a<0.05), so it can be concluded that there is an influence of brisk walking exercise intervention on reducing high blood pressure in hypertensive patients who take hypertension medication at Posbindu Gemaharjo. It is hoped that Posbindu Gemaharjo will routinely provide exercise therapy interventions in the form of the Brisk Walking Exercise for patients with hypertension, so that the risks of complications related to hypertension can be managed properly.